SUNDA WIWITAN DI ERA POST-TRUTH: STRATEGI BERTAHAN KOMUNITAS LOKAL DI ERA GLOBALISASI - Jubba, Hasse; Adila, Nispi Amalia; Herianto, Herianto; Septiani, Triana (Jurnal Studi Agama dan Masyarakat, 2021)
The existence of the Sunda Wiwitan community in Cireundeu Traditional Village has been faced with the threat of massive technological advances. Massive penetration of technology has caused indigenous people to use and accept technology as a necessity. In line with this, this paper was to explain how the sustainability and survival strategy of Sunda Wiwitan people in post truth era. This paper was based on data collected through direct observation and interviews with five different informants by taking into account the characteristics of each. The result showed that there was a strong influence between technology and the existence of Sunda Wiwitan as indigenous people. Indigenous people were able to adapt to all existing openness. This study confirmed that today's indigenous people still prevented their customs. Therefore, the existence of local communities needed to be guaranteed through various schemes, including supporting regulations that were protective in nature.